PERBEDAAN RASIO PROFITABILITAS PADA PERUSAHAANPERUSAHAAN SEKTOR PERTANIAN DI BURSA EFEK INDONESIA - Salmah, Ninin Non Ayu (Fakultas Ekonomi Universitas IBA, 2017)
This study aims to determine the difference in the ratio of profitability as a measure offinancial performance between companies incorporated in the Agricultural Sector on theIndonesia Stock Exchange with the hypothesis test analysis technique difference of morethan two averages. Research population are companies listed on Indonesia StockExchange Agricultural Sector. Research sample is PT. Bisi International Tbk, PT.Dharma Samudera Fishing Industries Tbk and PT. Astra Agro Lestari Tbk. The highestaverage ratio is obtained by PT. Astra Agro Lestari Tbk such as return on asset ratioequal to 11,8200%, return on equity ratio equal to 17,1180% as well net profit marginratio equal to 14,6380%. Hypothesis test of difference of more than two averageconcluded that the average return on asset ratio on companies incorporated in theAgricultural Sector on the Indonesia Stock Exchange differs significantly, the averagereturn on equity ratio on companies incorporated in the Agricultural Sector on theIndonesia Stock Exchange differs significantly and the average net profit margin ratio oncompanies incorporated in the Agricultural Sector on the Indonesia Stock Exchangediffers significantly.